2017
DOI: 10.1002/cncr.30598
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of extranodal extension in human papillomavirus‐associated oropharyngeal squamous cell carcinoma

Abstract: ENE is associated with inferior OS in patients with HPV-positive OPSCC. However, OS was not better with adjuvant chemoradiotherapy compared with radiotherapy alone in ENE-positive patients. The current findings support the need for prospective studies of adjuvant chemoradiation in HPV-positive patients with ENE. Cancer 2017;123:2762-72. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(131 citation statements)
references
References 23 publications
7
120
2
Order By: Relevance
“…Other recent studies have also demonstrated that ENE is a significant prognosticator in HPV‐positive OPSCC . The authors of these articles found ENE to confer a modest decrement in overall survival of 4% to 7%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other recent studies have also demonstrated that ENE is a significant prognosticator in HPV‐positive OPSCC . The authors of these articles found ENE to confer a modest decrement in overall survival of 4% to 7%.…”
Section: Discussionmentioning
confidence: 93%
“…Instead, the pathologic system relies only on the number of positive lymph nodes for HPV‐positive OPSCC, without consideration of ENE, nodal size, or laterality . The data from which the pathologic staging system was derived showed no statistically significant association between worse outcomes and ENE in HPV‐positive OPSCC; however, more recent studies are contradictory …”
Section: Introductionmentioning
confidence: 99%
“…Also, we provide evidence that orthotopically transplanted LNM recapitulates all the consecutive steps of LNM progression and are functionally reconnected with the host lymphatic system. 42,43 Nevertheless, our model conveys the potential to disclose the mechanistic and cellular basis of high-risk events within LNMs such as ECS. 22,[35][36][37] This approach has mostly been described in the nononcologic settings, specifically in the context of immunerelated questions, LN function and remodeling, and in preclinical models of postsurgical lymphedema.…”
Section: Molecular Cancer Biologymentioning
confidence: 97%
“…DOI, depth of invasion. [29]. Moreover, another retrospective evaluation did not report differences between stage I and stage II [30].…”
Section: Validity Of New Tnmmentioning
confidence: 99%
“…A significant advantage was also described for PFS (HR = 0.43, 95% CI: 0. 29 In HPV-positive tumours no difference was reported among stages I-III using the 7th edition because of their good prognosis [8]. O'Sullivan et al [9] reported 5-year OS for TNM stages I, II, III, and IVA: 88% (95% CI: 74-100), 82% (95% CI: 71-95), 84% (95% CI: 79-89), and 81% (95% CI: 79-83), respectively, in HPV-positive tumours with the 7th edition.…”
Section: Oropharyngeal Cancermentioning
confidence: 99%